2007
DOI: 10.1017/s0144686x07006253
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor environments for people with dementia: an exploratory study using virtual reality

Abstract: Few studies have investigated how outdoor environments might disable people with dementia. The issue is rarely considered in planning and design guidelines and not at all in regulations, despite dementia being within the scope of disability discrimination legislation in the United Kingdom and other countries. This article reports a study that involved older people with mild to moderate dementias taking two walks, one in a real town centre and one in a virtual reality (VR) simulation. Adaptations were made to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 15 publications
2
63
0
2
Order By: Relevance
“…Many of the critical incidents described in this study confirm findings from earlier studies, for example difficulties in distinguishing between a road and a pedestrian path, difficulties in observing changes in levels (25), and being exposed to heavy traffic, difficulties in using maps for navigation (4,25) and in using everyday technology (26).…”
Section: Discussionsupporting
confidence: 85%
“…Many of the critical incidents described in this study confirm findings from earlier studies, for example difficulties in distinguishing between a road and a pedestrian path, difficulties in observing changes in levels (25), and being exposed to heavy traffic, difficulties in using maps for navigation (4,25) and in using everyday technology (26).…”
Section: Discussionsupporting
confidence: 85%
“…Another study concerned with way-finding and urban design by Blackman et al 57 and Van Schaik et al 68 used a virtual environment to assess how different environmental features affected how people with dementia journeyed through a city setting. The research demonstrated that such technology can be used to support people with dementia in evaluating urban environments.…”
Section: Built Environmentmentioning
confidence: 99%
“…[54][55][56] There is also work that suggests that 'walking' helps to (at least) maintain cognitive functioning in those with dementia 19,56 and that the practicalities of getting 'out and about' in neighbourhoods, such as through navigating local environments, plays a pivotal role in maintaining a person with dementia's sense of self and well-being. 1,19,[57][58][59][60][61] Such environmental issues are important dimensions of neighbourhood living. The review on promoting cognitive health and vitality by Yevchak et al 62 clearly demonstrated the importance of older people maintaining social engagement, contacts and stimulation.…”
Section: Outdoor Spacesmentioning
confidence: 99%
“…Smart phones with GPS and map functions, offer functionality to support wayfinding [50], including identifying indicators of disorientation to support navigation prompting [51]. For those who have difficulty getting out or participating in regular exercise, virtual cycling [52] and navigating virtual environments [53] can offer enjoyable alternatives.…”
Section: Introductionmentioning
confidence: 99%